Issledovanie transformacii norm Edinoj vserossijskoj sportivnoj klassifikacii po velosipednomu sportu v gruppe disciplin «šosse» - Kubeev, A. V.; Oganesyan, A. A.; Mochalova, M. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
We studied the standards for the performance of sports categories and sports ranks and the conditions for their implementation of the Unified All-Russian Sports Classification (hereinafter referred to as the UARSC) for cycling in the Road discipline, as well as the means and methods of making changes and additions to the UARSC. The peculiarities of the construction and subsequent action of the UARSC on the development processes of cycling in the Russian Federation objectively indicate the need to fully take into account the volume and quality of all data associated with the various registers of the UARSC: sports disciplines of cycling, age and gender groups of athletes, status and name of sports competitions and physical educationevents, sports categories and sports titles. The success factor in the development of UARSC is largely in the transition to a digital basis for modeling and taking into account the dynamics of growth of sportsmanship, taking into account objective and reasonable trends in the growth of sports results at all levels of sports training.